Potato Flour Subsitution On Nastar Quality - Tin, Nur Hidayas; Anggraini, Ezi (Universitas Negeri Padang, 2023)
This research is motivated by the use of potato starch to vary nastar by substitution with potato flour which aims to utilize local food ingredients, adding to the innovation of nastar products. This study aims to analyze the effect of substitution of potato starch as much as 15%, 30% and 45% on the quality of nastar in terms of shape, color, aroma, texture and taste. The main ingredient in making nastar is wheat flour which is still imported. This type of research is an experimental method with Completely Randomized Design (CRD). The data used are primary data obtained directly from 3 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of potato starch nastar. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results showed that the substitution of potato flour had an effect on the quality of the aroma and taste of potatoes in nastar, while for the quality of shape, color, texture and sweetness there was no significant effect. The results of the best quality test of potato starch nastar are in the X2 and X3 treatment with 30% and 45% potato starch substitution.